1993
DOI: 10.1007/bf00171892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dispersed oil on heterotrophic bacterial communities in cold marine waters

Abstract: Mesocosm studies were conducted to evaluate the effect of dispersed oil on total and heterotrophic bacterial communities of under-ice seawater from the St. Lawrence Estuary. A regular survey of bacterial changes in the oil-contaminated seawater was performed during a two week period. The bacterial community structure was investigated by carrying out 27 morphological and biochemical tests on 168 isolated strains. The results show a detectable but transient response of the bacterial community to crude oil additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
2
5
2
1
Order By: Relevance
“…At first, abundance values were within the range observed before the spill. This result agrees with other field studies in open waters (Delille & Siron 1993) but contrasts with those reported for laboratory experiments with oil-treated microcosms, in which total number of bacteria increased significantly after contamination with water soluble hydrocarbons (Medina-Bellver et al 2005, Sargian et al 2005. Such difference could be due not only to the variable toxicity of the different hydrocarbons involved in each case study, but also to their concentrations and time of exposure for the bacterioplankton.…”
Section: Bacterioplankton Responsesupporting
confidence: 87%
See 1 more Smart Citation
“…At first, abundance values were within the range observed before the spill. This result agrees with other field studies in open waters (Delille & Siron 1993) but contrasts with those reported for laboratory experiments with oil-treated microcosms, in which total number of bacteria increased significantly after contamination with water soluble hydrocarbons (Medina-Bellver et al 2005, Sargian et al 2005. Such difference could be due not only to the variable toxicity of the different hydrocarbons involved in each case study, but also to their concentrations and time of exposure for the bacterioplankton.…”
Section: Bacterioplankton Responsesupporting
confidence: 87%
“…At the same time, hydrocarbon-degrading bacteria often increase their relative abundance in natural communities after an oil spill (Maruyama et al 2003, Bordenave et al 2004. Changes in total abundance and production of natural bacterioplankton communities in relation to oil spills, however, are rarely reported (Delille & Siron 1993, Piehler et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports show that increasing crude oil concentration decreased the microbial population of the soil (Delille and Siron 1993). On the contrary, our results showed that in the presence of high concentration of crude oil (10 and 7 %), the microbial population and oil degrading bacteria, increased in comparison with the control and lower concentrations of crude oil (1 and 3 %).…”
Section: Discussioncontrasting
confidence: 82%
“…Leur présence dans les eaux froides de l'estuaire du Saint-Laurent a été démontrée (Delille et Siron, 1993) et pourrait être liée aux quelque 1 900 évents naturels de méthane répertoriés par Lavoie et collab. (2010) dans l'estuaire.…”
Section: Eaux Froides Et Dégradation Bactérienneunclassified